Pengaruh Konflik Kerja dan Stres Kerja Terhadap Kinerja Karyawan di PT Bama Berita Sarana Televisi (BBSTV Surabaya) - Linda Marista (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2018)
PT. Bama Berita Sarana Televisi (BBS TV Surabaya) in entertainment industry, found a problem of low employee performance. The purpose of this study was to determine the influence of conflict and work stress partially and simultaneously on employee performance. This research is quantitative research with a total sample of 63 respondents who are employees of PT Bama Berita Sarana Televisi (BBSTV Surabaya) by using saturated sampling techniques. Based of the result of calculation SPSS version 23 conflict have partially and negative significant on employee performance with t hitung -3,699 >Ttabel 1,670 with the significance value 0,000 which mean < 0,05. Partially there is an influence between conflict with employee performance. Work stress have partially and negative significant on employee performance with thitung = - 2,242 > 1,670 with value 0,029<0,05. Conflict and work stress simultaneously affect employee performance with results F 8,532>Ftabel 3,15 with significance value 0,001 which mean significance value < 0,05.